Retaliation : - Webber, Bert (Oregon State University Press, 1975)
This book is designed to unscramble and assemble pertinent details and anecdotes about the attacks and the circumstances surrounding them. It deals generally with Japanese operations off the west coast of the United States and Canada, with defense measures taken to lessen their effects, and with Japanese attems to strike blows into the American homeland as reliation for the Doolittle raid on the Japanese homeland.